Respostas
respondido por:
1
x - y = 2
-2x + y = 1
==========
-x = 3 . (-1)
x = -3
x - y = 2
-3 - y = 2
-y = 2 + 3
-y = 5 . (-1)
y = -5
s={ -3, -5 }
☆Espero ter ajudado!
-2x + y = 1
==========
-x = 3 . (-1)
x = -3
x - y = 2
-3 - y = 2
-y = 2 + 3
-y = 5 . (-1)
y = -5
s={ -3, -5 }
☆Espero ter ajudado!
ana16102:
Ajudou sim
respondido por:
2
x - y = 2
-2x + y = 1
------------------ SOMA
-x = 3
x = -3
x - y = 2
-3 - y = 2
-y = 5
y = -5
-2x + y = 1
------------------ SOMA
-x = 3
x = -3
x - y = 2
-3 - y = 2
-y = 5
y = -5
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás